Design, implementation and evaluation of an intervention based on a social cognitive theory of physical activity and nutritional behaviors in middle-aged people at the risk of coronary artery disease in Bandar Abbas: A study protocol - Roghayeh Ezati Rad; Zahra Hosseini; Shokrollah Mohseni; Mohammad Mohammadi; Marzieh Nikparvar; Teamur Aghamolaei (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Coronary artery disease (CAD) is the most common cardiovascular disease (CVD) and the main cause of mortality in developed and developing countries. Physical activity and nutritional behaviors are modifiable factors in people at the risk of CAD and its risk factors; thus, the present study aimed to design, implement, and evaluate an intervention based on the social cognitive theory for physical activity and nutritional behaviors in the middle-aged population at the risk of CAD residing in Bandar Abbas city. MATERIALS AND METHODS: The present study will be conducted in three phases: qualitative, cross-sectional, and community-based intervention. The middle-aged population with less than 150 minutes of physical activity a week with at least one other risk factor of CAD (hyperlipidemia, hypertension, diabetes, overweight and obesity, smoking) will be included in the study. In the qualitative phase of study, the participants will be selected with maximum diversity and with the aim of obtaining comprehensive information to clarify the nature and dimensions of the phenomenon in question. The cross-sectional phase aimed to determine the intensity of physical activity and nutritional behaviors. By analyzing the data obtained from the cross-sectional phase, the most important constructs of the social-cognitive theory in physical activity and nutritional behaviors will be determined, and accordingly, an effective intervention will be designed. The third phase of the pre-test-post-test intervention study will include a randomized control group. The interventions will be a combination of face-to-face meetings and the use of educational technologies. Individuals in the control group will not undergo the educational intervention. Those in the intervention group will be evaluated in two phases (before the implementation of the intervention, and 3 months after the intervention). CONCLUSION: The findings of the present study can be used as a strategic plan to help policy makers to strengthen CVD prevention and management alternatives to include physical activity and nutritional behavior as part of their preventive measures.